2021
DOI: 10.1002/ccr3.3856
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hemiagenesis with primary hyperparathyroidism or papillary thyroid carcinoma: A report of two cases and literature review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Alqahtani et al previously reported 13 cases of thyroid hemiagenesis in association with primary hyperparathyroidism in the English language literature. 11 This case is 14th case of thyroid hemiagenesis in association with hyperparathyroidism. Previous patients had primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Alqahtani et al previously reported 13 cases of thyroid hemiagenesis in association with primary hyperparathyroidism in the English language literature. 11 This case is 14th case of thyroid hemiagenesis in association with hyperparathyroidism. Previous patients had primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 85%
“…Thyroid hemiagenesis is an extremely rare developmental disorder of the thyroid, 10 but it may become apparent during surveillance for thyroid diseases such as thyroid tumor, carcinoma, or Graves' disease. [9][10][11] Thyroid hemiagenesis is caused by one side of the thyroid not developing embryologically, rather than a failure of glandular tissue descent or migration, as seen in ectopic thyroid. 7,30 Regarding laterality, past reports have shown many cases of thyroid hemiagenesis are on the left side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many times, patients are euthyroid and hemiagenesis of a thyroid lobe found incidentally. However, patients with thyroid hemiagenesis have higher incidence of coexisting thyroid disorders in the remaining lobe including Graves disease, 4 Hashimoto thyroiditis, 5 multinodular goiter, 1 subacute thyroiditis, 6 papillary or medullary thyroid carcinoma, 7,8 and primary hyperthyroidism. 8 The patient in this case presented with low thyroid-stimulating hormone, normal T3 and T4 levels, and low uptake in the remaining right thyroid lobe, suggesting subacute thyroiditis.…”
Section: Figurementioning
confidence: 99%
“…However, patients with thyroid hemiagenesis have higher incidence of coexisting thyroid disorders in the remaining lobe including Graves disease, 4 Hashimoto thyroiditis, 5 multinodular goiter, 1 subacute thyroiditis, 6 papillary or medullary thyroid carcinoma, 7,8 and primary hyperthyroidism. 8 The patient in this case presented with low thyroid-stimulating hormone, normal T3 and T4 levels, and low uptake in the remaining right thyroid lobe, suggesting subacute thyroiditis. The plan is to follow up her thyroid function tests in 6 to 8 weeks to assess for chronic thyroiditis if her thyroid function does not return to normal.…”
Section: Figurementioning
confidence: 99%